ANALISIS PETANI JAGUNG DALAM MEMANFAATKAN SARANA PRODUKSI DI DESA PILOMONU KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Yusriyah Atikah Gobel; Moch. Muchlis Djibran; Abdul Kadir G. Djamil (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2022)
ABSTRACTThe purpose of this study was to determine the production facilities used by corn farmer groups and the behaviour of farmer group members in utilising production facilities in Pilomonu village, Mootilango district, Gorontalo district. The results showed that the production facilities used by farmer groups in Pilomonu Village, Mootilango Subdistrict, were considered very good, namely the use of superior seeds could increase productivity. Seeds were the decisive stage in the entire cycle of agricultural activities. The dose, time, and method of using fertilisers affected the productivity of corn plants. OPTs and pests can reduce the productivity of agricultural crops. The need for pesticides must be in accordance with the area of land planted. The dose, time, and method of using pesticides affect the productivity of corn plants. Recognizing signs of plants that are lacking sufficient excess pesticides is knowledge that must be owned by farmers. Agricultural mechanisation can increase farm productivity. Seeds, fertilizers, pests and pesticides, as well as agricultural mechanization, are good for increasing corn production facilities in Pilomonu VillageKey words: Behavior, Corn , Farmers, Means Of Production.ABSTRAKTujuan penelitian ini adalah untuk mengetahui sarana produksi yang dimanfaatkan kelompok tani jagung dan perilaku anggota kelompok tani dalam memanfaatkan sarana produksi di desa Pilomonu Kecamatan Mootilango Kabupaten Gorontalo. Dari hasil penelitian menunjukkan bahwa sarana produksi yang dimanfaatkan kelompok tani di Desa Pilomonu Kecamatan Mootilango yang dianggap sangat baik yaitu penggunaan benih unggul dapat meningkatkan produktivitas, benih merupakan tahap menentukan dalam seluruh siklus kegiatan pertanian, dosis, waktu dan cara penggunaan pupuk berpengaruh terhadap produktivitas tanaman jagung, OPT/hama dapat menurunkan produktivitas tanaman pertanian, kebutuhan pestisida harus sesuai dengan luas lahan yang ditanami, dosis, waktu dan cara penggunaan pestisida berpengaruh terhadap produktivitas tanaman jagung, mengenali tanda-tanda tanaman yang kurang, cukup, kelebihan pestisida merupakan pengetahuan yang harus dimiliki petani dan mekanisasi pertanian dapat meningkatkan produktivitas usahatani.Benih, pupuk, OPT dan pestisida serta mekanisasi pertanian tergolong baik untuk meningkatkan sarana produksi tanaman jagung di Desa Pilomonu.Kata kunci: Jagung, Perilaku, Petani, Sarana Produksi.